2020
DOI: 10.1039/d0gc02205e
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of hydroxyl-containing oxindoles and 3,4-dihydroquinolin-2-ones through oxone-mediated cascade arylhydroxylation of activated alkenes

Abstract: Hydroxyl-containing compounds are highly value-added organic molecules, and the establishment of novel methodologies for their elaboration is a long-standing challenge in organic synthesis. Here the first oxone-mediated direct arylhydroxylation of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 59 publications
2
12
0
Order By: Relevance
“…[17d] Our group reported an intra-molecular trans-arylhydroxylation of tertiary α,β-unsaturated amides for the synthesis of hydroxyl-containing oxindoles and 3,4-dihydroquinolin-2-ones (Scheme 1C, a). [18] A two-step one-pot intermolecular hydroxyazidation of α,β-unsaturated amides was also reported by Ohshima, Shibasaki and co-workers in 2005 (Scheme 1C, b). [19] Inspired by these works, we envisaged that the direct trans-dihydroxylation of α,β-unsaturated amides might be realized through in situ generation of epoxides under suitable reaction conditions.…”
Section: Introductionsupporting
confidence: 56%
“…[17d] Our group reported an intra-molecular trans-arylhydroxylation of tertiary α,β-unsaturated amides for the synthesis of hydroxyl-containing oxindoles and 3,4-dihydroquinolin-2-ones (Scheme 1C, a). [18] A two-step one-pot intermolecular hydroxyazidation of α,β-unsaturated amides was also reported by Ohshima, Shibasaki and co-workers in 2005 (Scheme 1C, b). [19] Inspired by these works, we envisaged that the direct trans-dihydroxylation of α,β-unsaturated amides might be realized through in situ generation of epoxides under suitable reaction conditions.…”
Section: Introductionsupporting
confidence: 56%
“…15 Also, some strategies include domino Heck/borylation (Scheme 1a) 16 and aminooxyarylation of N -arylacrylamides (Scheme 1a), 17 which give intermediates that require one more step and a longer reaction time to obtain the desired products. Recently, He et al reported oxone-mediated arylhydroxylation of N -arylacrylamides (Scheme 1a), 18 but it suffers from regioselectivity. In this context, we are developing commercially viable and transition metal-free protocols using a green reagent “rongalite” in the presence of a mild base.…”
Section: Introductionmentioning
confidence: 99%
“…Among these reactions, the arylhydroxylation of alkenes that introduce vital aryl and hydroxyl groups across the double bonds has attracted considerable interest. In contrast with intramolecular arylhydroxylation, intermolecular arylhydroxylation of alkenes to afford β-arylethylalcohol-based acyclic molecules is still a particularly difficult challenge because of the issues with regiocontrol.…”
mentioning
confidence: 99%